If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4 + -3x) + -3(2x + 1) = 7(5x + 2) + -103 (4 * 2 + -3x * 2) + -3(2x + 1) = 7(5x + 2) + -103 (8 + -6x) + -3(2x + 1) = 7(5x + 2) + -103 Reorder the terms: 8 + -6x + -3(1 + 2x) = 7(5x + 2) + -103 8 + -6x + (1 * -3 + 2x * -3) = 7(5x + 2) + -103 8 + -6x + (-3 + -6x) = 7(5x + 2) + -103 Reorder the terms: 8 + -3 + -6x + -6x = 7(5x + 2) + -103 Combine like terms: 8 + -3 = 5 5 + -6x + -6x = 7(5x + 2) + -103 Combine like terms: -6x + -6x = -12x 5 + -12x = 7(5x + 2) + -103 Reorder the terms: 5 + -12x = 7(2 + 5x) + -103 5 + -12x = (2 * 7 + 5x * 7) + -103 5 + -12x = (14 + 35x) + -103 Reorder the terms: 5 + -12x = 14 + -103 + 35x Combine like terms: 14 + -103 = -89 5 + -12x = -89 + 35x Solving 5 + -12x = -89 + 35x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-35x' to each side of the equation. 5 + -12x + -35x = -89 + 35x + -35x Combine like terms: -12x + -35x = -47x 5 + -47x = -89 + 35x + -35x Combine like terms: 35x + -35x = 0 5 + -47x = -89 + 0 5 + -47x = -89 Add '-5' to each side of the equation. 5 + -5 + -47x = -89 + -5 Combine like terms: 5 + -5 = 0 0 + -47x = -89 + -5 -47x = -89 + -5 Combine like terms: -89 + -5 = -94 -47x = -94 Divide each side by '-47'. x = 2 Simplifying x = 2
| 254=139-y | | 4a^3bx-4bx= | | tan(-x)=5/8 | | 8(0+2y)=16(30-4y) | | 9/-4=-2 | | 8x-34+118=180 | | 6x-0=-16 | | 0.5x-0.4y=2.6 | | -0.75+0.4= | | m^2+23m+24=1 | | 2(r+-130)+2r=1660 | | 3y+15x=24 | | 0.2x+0.3y=1.5 | | 5x+2(x-1)=6x-2 | | 3(r+-180)+3r=2340 | | -6f=-20 | | 3(r+-180)+4r=2340 | | a^3-6a^2= | | 16/9=x2 | | 20+6= | | 7x/3= | | M/3-4=12 | | 6m+10-10= | | 5-z=-5 | | 6m+3t+4-4m-2t= | | H=8+17 | | 49x+3x+x+12= | | x/9x-12=15 | | 0.25f+0.5=4.5 | | 31=5(1+3m)-2m | | 4(r-110)+4r=3400 | | -5/2x=6 |